2015
DOI: 10.1371/journal.pone.0137795
|View full text |Cite
|
Sign up to set email alerts
|

Mannan-Binding Lectin Is Involved in the Protection against Renal Ischemia/Reperfusion Injury by Dietary Restriction

Abstract: Preoperative fasting and dietary restriction offer robust protection against renal ischemia/reperfusion injury (I/RI) in mice. We recently showed that Mannan-binding lectin (MBL), the initiator of the lectin pathway of complement activation, plays a pivotal role in renal I/RI. Based on these findings, we investigated the effect of short-term DR (30% reduction of total food intake) or three days of water only fasting on MBL in 10–12 weeks old male C57/Bl6 mice. Both dietary regimens significantly reduce the cir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 44 publications
2
10
0
Order By: Relevance
“…In this study, we have chosen the 8-week DR protocol for old animals. Since in young rats 4 weeks of DR had a very pronounced nephroprotective effect [ 30 ] which was consistent with other studies [ 15 , 51 ], we did not change the details of this protocol besides its length. The majority of papers dealing with a short-term DR in old rodents used 8 weeks of DR and it resulted in a range of beneficial consequences.…”
Section: Discussionsupporting
confidence: 77%
“…In this study, we have chosen the 8-week DR protocol for old animals. Since in young rats 4 weeks of DR had a very pronounced nephroprotective effect [ 30 ] which was consistent with other studies [ 15 , 51 ], we did not change the details of this protocol besides its length. The majority of papers dealing with a short-term DR in old rodents used 8 weeks of DR and it resulted in a range of beneficial consequences.…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, lifestyle factors can also impact MBL. Fasting and dietary restrictions reduce circulating levels of MBL as well as mRNA expression in liver [ 39 ], However, after adjustment MBL for these confounders levels remained associated with cardiovascular events, indicating a direct and independent effect of MBL on cardiovascular risk. This study revealed that MBL levels are the same in HD patients and healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, MBL-A and MBL-C are serum proteins that are mainly synthesised by the liver and small intestine (Ezekowitz et al 1988 ; Sastry et al 1991 ; Hansen et al 2000 ) (Table 1 ). In mice, mRNA expression of MBL genes was also detected in various other tissues (Shushimita et al 2015 ), and this may also be these case for Bovidae, particularly the rumen and udder. The normal serum concentrations of bovine MBL-A and MBL-B have not been clearly defined but are estimated to be 0.8–7.4 μg/mL (Wang et al 2012 ).…”
Section: Tissue Distribution Physiological Role and Protection Agaimentioning
confidence: 87%